2013
DOI: 10.1149/2.005304ssl
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exposure to Ultraviolet-Activated Oxygen on the Electrical Characteristics of Amorphous Indium Gallium Zinc Oxide Thin Film Transistors

Abstract: An exposure of the back channel of an indium gallium zinc oxide (IGZO) thin film transistor (TFT) to ultraviolet (UV)-activated oxygen can effectively shift the threshold voltage (V th ) of the TFT. The V th decreases linearly with the exposure time while the on-state current greatly increase with the exposure time. The exposure doesn't have a strong impact on other device parameters. The effect of the exposure on the V th is attributed to the increase in the electron concentration of the channel layer as a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Further, in both samples, V TH is negatively shifted, which suggests that a decrease in the charge trap took place, increasing the intrinsic carrier in the a-IGZO films. Because oxygen vacancy in the a-IGZO causes an intrinsic carrier [9], the results shows that oxygen vacancy is increased by photo irradiation. Because the increase in mobility and V TH shift simultaneously occurred, we concluded that a decrease in the electron trap took place the V TH shift.…”
Section: Methodsmentioning
confidence: 92%
“…Further, in both samples, V TH is negatively shifted, which suggests that a decrease in the charge trap took place, increasing the intrinsic carrier in the a-IGZO films. Because oxygen vacancy in the a-IGZO causes an intrinsic carrier [9], the results shows that oxygen vacancy is increased by photo irradiation. Because the increase in mobility and V TH shift simultaneously occurred, we concluded that a decrease in the electron trap took place the V TH shift.…”
Section: Methodsmentioning
confidence: 92%
“…Meanwhile, the behavior of the TFT no longer obeyed the logarithmic time dependence model with longer exposure to the UV irradiation to 60 min (R 2 ¼ À0.259 and r 0 ¼ 0.17), which is ascribed to the removal of the interface traps to sufficiently low level to prevent the device deterioration under prolonged bias stress. The beneficial effect of the UV irradiation on the device performances as observed above can first be attributed to the removal of organics and carbon contaminations on the surfaces of SiO 2 dielectric by activated oxygen or ozone formed by the UV irradiation in oxygen-containing ambient [20,21]. It is known that ozone can remove the surface contaminants by its strong oxidation power and this results in the preparation of atomically clean surface [20].…”
Section: Mechanisms Of V Th Shift and Degradationmentioning
confidence: 96%
“…The beneficial effect of the UV irradiation on the device performances as observed above can first be attributed to the removal of organics and carbon contaminations on the surfaces of SiO 2 dielectric by activated oxygen or ozone formed by the UV irradiation in oxygen-containing ambient [20,21]. It is known that ozone can remove the surface contaminants by its strong oxidation power and this results in the preparation of atomically clean surface [20]. If the channel layer is deposited on such a clean surface of SiO 2 dielectric, it is expected that interface trap states related to the surface adsorbates can be removed substantially.…”
Section: Mechanisms Of V Th Shift and Degradationmentioning
confidence: 96%
“…These peaks correspond to stoichiometric oxygen in the hybrid YIZO films (O1), oxygen vacancies in the hybrid YIZO films (O2), and the oxygen loosely bonded at the surfaces of the hybrid YIZO films (O3). 12 The O2/O1 ratio indicates the relative number of oxygen vacancies, and the values of this ratio are 24.65% and 51.86% for the hybrid YIZO films with and without UV irradiation, respectively. These values can be explained by the fact that the oxygen vacancies, which are the origin of the low mobility, were decreased by the application of UV irradiation in the hybrid YIZO system because the UV-cured film affects the channel alignment and densifies the channel.…”
Section: Uv-cured Reactive Mesogen-yinzno Hybrid Materials Asmentioning
confidence: 99%
“…These values can be explained by the fact that the oxygen vacancies, which are the origin of the low mobility, were decreased by the application of UV irradiation in the hybrid YIZO system because the UV-cured film affects the channel alignment and densifies the channel. 12,13 We then measured the optical retardation of the hybrid YIZO films with and without UV irradiation to trace the aligned channel material, as shown in Figure 3. Optical-retardation measurements can evaluate and be used to determine the anisotropy of hybrid YIZO films with and without UV irradiation.…”
Section: Uv-cured Reactive Mesogen-yinzno Hybrid Materials Asmentioning
confidence: 99%